Pengaruh Kepemimpinan Kepala Sekolah Terhadap Kinerja Guru di SMK Negeri 1 Suwawa - Ruth Unaiya; Usman Moonti; Sudirman Sudirman (Journal of Economic and Business Education, 2023)
This research employs a quantitative approach. The data are primary data obtained from the distribution of questionnaires to the educators and educational staff osf SMK Negeri 1 Suwawa, Bone Bolango Regency, Gorontalo Province. The number of samples in this research is 58 respondents. The data are analyzed through Simple Linear Regression. The results indicate that there is an influence of school principal leadership on Teacher Performance at SMK 1 Suwawa, Bone Bolango Regency, Gorontalo Province. The magnitude of the influence of the school principal’s leadership on teacher performance at SMK Negeri 1 Suwawa, Bone Bolango Regency, Gorontalo Province is 65,3%, while unexamined variables influence the remaining 34,7%.